Tumor arthroplasties performed after proximal femur pathological fractures and evaluation of their pelvic parameters (Annals of Medical Research, 2022)
Aim: Our aim in this study is to analyze patients who underwent arthroplasty for pathological fractures of the proximal femur and examine pelvic parameters in eligible patients.Material and Methods: Age, gender, operation side of the patients, the area of the fracture in the proximal femur previous lumbar spine surgery, lumbar region metastasis, postoperative leg length difference, postoperative dislocation, whether revision was performed and the appropriate patient.Results: 32 patients who underwent arthroplasty for pathological fracture of the proximal femur were identified. Dislocation was observed in 2 (6%) patients in the postoperative follow-up. The indication for the patient undergoing revision surgery was periprosthetic fracture after a fall. In 7 of the patients, the cause of the pathological fracture was primary bone tumor, while 24 of them were metastasis. The mean PI of these patients whose measurements were made from the lateral lumbar graphy were 54°, mean SD: 38°, mean PT: 11° and mean lumbar lordosis: 30°.Conclusion: Arthroplasty can be successfully applied as an extremity-conserving surgery method in patients with proximal femur pathological fractures, and the preoperative health status and life expectancy of the patient also affect the results of the surgery.
Keywords: Tumor arthroplasty; pathological fracture; pelvic parameter; proximal femur